The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/anie.201809167
|View full text |Cite
|
Sign up to set email alerts
|

Specific and Oriented Encapsulation of Fullerene C70 into a Supramolecular Double‐Decker Cage Composed of Shape‐Persistent Macrocycles

Abstract: An efficient strategy for the specific recognition of ellipsoidal fullerenes uses molecular containers with well-designed three-dimensional (3D) nanospaces. We describe the synthesis of a supramolecular double-decker cage composed of shape-persistent metallomacrocycles and pillar ligands. A discrete 3D nanospace was built within the molecular framework of the shape-persistent-macrocycle/bidentate-pillar molecule. The single-crystal structure of the supramolecular cage reveals a uniquely shaped inner cavity wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 62 publications
1
27
0
Order By: Relevance
“…Covalently bondeds ystemsa re quite common, for example,c yclodextrins, cucurbiturils and cryptands which bind cations, [8] anions, [9] or hydrophobic molecules [10] by variation of their peripherald ecoration.T oroidal coordination cages are also able to bind guest molecules and separate fullerenes. [11] These systems are challenging to model using density functionalt heory (DFT) due to their large size. Herein we demonstrate not only that ag eometry-optimized structure of al arge emptym etallacycle can be obtained,b ut also the C 60 and C 70 Figure 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Covalently bondeds ystemsa re quite common, for example,c yclodextrins, cucurbiturils and cryptands which bind cations, [8] anions, [9] or hydrophobic molecules [10] by variation of their peripherald ecoration.T oroidal coordination cages are also able to bind guest molecules and separate fullerenes. [11] These systems are challenging to model using density functionalt heory (DFT) due to their large size. Herein we demonstrate not only that ag eometry-optimized structure of al arge emptym etallacycle can be obtained,b ut also the C 60 and C 70 Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Covalently bonded systems are quite common, for example, cyclodextrins, cucurbiturils and cryptands which bind cations, anions, or hydrophobic molecules by variation of their peripheral decoration. Toroidal coordination cages are also able to bind guest molecules and separate fullerenes …”
Section: Introductionmentioning
confidence: 99%
“…We expect that tuning of the electronic density on the interacting hydrogen or other atoms by the introduction of functional groups should influence the association property. Recently, a double‐decker disk‐type ring consisting of dibenzothiophene macrocycles and metal ions was reported by Tanaka et al . This approach is promising to increase the contact sites for CH–π interactions.…”
Section: Discussionmentioning
confidence: 71%
“…[79] For the complexeso f disk-typer ings, the association constants are not so high because of the narrow contact area. We expect that tuningo ft he electronic density on the interacting hydrogen or other atoms by the introduction of functional groups should influence the association property.R ecently,adouble-decker disk-typer ing consisting of dibenzothiophene macrocycles and metal ions was reported by Ta naka et al [80] This approachi sp romising to increaset he contact sites for CH-p interactions. Some beltshaped rings exhibited high complexation selectivity for C 60 and C 70 ,b ut the selectivity was relativelyl ow for disk-type rings so far reported.…”
Section: Discussionmentioning
confidence: 89%
“…Tanaka et al reported a double-decker macrocycle with 32 H atoms directed inward potentially. [11] Another way to realize such a structure is by constructing a cage-type framework so as to surround a guest molecule, which is well known as the cryptate effect in supramolecular chemistry. [12] There are a large number of cage-type hosts that include guest molecules effectively by preorganized multipoint recognition.…”
Section: Introductionmentioning
confidence: 99%